2020
DOI: 10.3390/molecules25132975
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanocellulose-Copper (II) Oxide as Engine Oil Additives for Tribological Behavior Improvement

Abstract: Friction and wear are the main factors in the failure of the piston in automobile engines. The objective of this work was to improve the tribological behaviour and lubricant properties using hybrid Cellulose Nanocrystal (CNC) and Copper (II) oxide nanoparticles blended with SAE 40 as a base fluid. The two-step method was used in the hybrid nanofluid preparation. Three different concentrations were prepared in a range of 0.1% to 0.5%. Kinematic viscosity and viscosity index were also identified. The fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Along with the improvement of the tribological behaviour, it has been shown that some nanomaterial additives can significantly improve lubrication performance by enhancing the thermal stability of the lubricant [ 6 , 7 ], all of which have a significant impact on fuel consumption. In addition, nanomaterials are relatively resistant to temperature, making them an interesting alternative or complement to traditional additives [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the improvement of the tribological behaviour, it has been shown that some nanomaterial additives can significantly improve lubrication performance by enhancing the thermal stability of the lubricant [ 6 , 7 ], all of which have a significant impact on fuel consumption. In addition, nanomaterials are relatively resistant to temperature, making them an interesting alternative or complement to traditional additives [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The review of the literature shows that there are very few studies using fully formulated engine oils [ 20 ], since they focus on lubricant baseoils [ 8 , 9 , 21 , 22 ], so the impact that functionalized ZnO nanomaterials have not only on tribological performance but also on how these metal oxide nanomaterials interact with other conventional antioxidants such as zinc dialkyldithiophosphates (often referred to as ZDDP) [ 23 ] and other types of additives in engine oils, is unclear.…”
Section: Introductionmentioning
confidence: 99%